TAKING WOMEN’S RIGHTS SERIOUSLY: WOMEN’S STRUGGLE FOR A NEW “SOCIAL CONTRACT” IN POLAND - Śledzińska-Simon, Anna; Wójcik, Anna (Pravni zapisi, 2024)
The article traces the trajectory of the struggle for woman’s rights in Poland from 1989 to the present. It argues that the democratic transition successfully shaped the foundations of a liberal regime, but was accompanied from the outset by an agreement between the government and the Catholic Church that limited reproductive rights and led to a retraditionalization of gender roles. This context is crucial to understanding the Constitutional Tribunal’s interpretation of the constitution, which reinforced a kind of sexual contract, seeking to domesticate women. The change of government in 2015 significantly weakened guarantees of the rule of law and further curtailed reproductive rights, prompting mass protests and the mobilization of democratic opposition. This article posits that the overthrow of the illiberal regime in the recent parliamentary elections marks the beginning of a new social contract in Poland, in which woman’s rights are taken seriously.
Keywords: Democratization; Democratic backsliding; Poland; Constitutional Tribunal; Women's right; Abortion; Reproductive rights; Social contract